PENGARUH FAKTOR FINANCIAL DAN NON FINANCIAL TERHADAP TINGKAT UNDERPRICING PADA PERUSAHAAN SEKTOR CONSUMER - Maylani, Fadilla Rahma; Sudiman, Josephine; Heriyanto, Randy (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research was conducted to evaluate the impact of financial factors and non-financial factors that can cause the phenomenon of underpricing. The method adopted in this research is a quantitative approach. The research population includes all companies that conducted an initial public offering between 2016 and 2022. The sample was selected using a purposive sampling method with a total of 98 companies. Statistical analysis using multiple linear regression analysis techniques. Research findings show that individually net profit margin, total asset turnover and ownership retention have a negative influence on underpricing, while current ratio, company size and company age have no influence on underpricing. Together, current ratio, net profit margin, total asset turnover, ownership retention, company age and company size have an influence on underpricing.